Pengaruh penggunaan asap cair terhadap masa simpan telur ayam ras yang di amati melaui cemaran mikroba, indeks kuning telur (ikt), indeks putih telur (ipt) dan haugh unit (hu). - Hendro Boimau; Annytha IR Detha; Diana A Wuri (Jurnal Veteriner Nusantara, 2019)
Food is the main and important source of the human needs stay alive. Good food is a food that free from all the type of contaminations. Based on the origin of the food, there is to type of food; food from animal origin and vegetable origin. Egg is one of the food from animal origin, which has high nutritional value, but easily damaged if not handled well, threfore egg must be handled with special treatment to extend the consumption period. Purpose of this research is to review the liquid smoke to determine the effect The purpose of this study was to determine the effect of liquid smoke to the eggs storage period were observed through microbial contamination, yolk index, egg white index and haugh unit and air sac. The egg samples used is 54 eggs of chicken with the age of 0 days and tests were conducted at the Laboratory of Animal Disease and Veterinary Public Health The Universty of Nusa Cendana, Kupang. The study design used is a randomized block design, where samples are divided into 3 group, control group, the Group immediately spray with liquid smoke and topical group as soon as with liquid smoke. Results is the used of liquid smoke has effect against future save the eggs seen on the microbiological quality of eggs that is able to maintain the future save of the eggs up to 25 days, but the liquid smoke has no effect on the future save of eggs viewed from the physical eggs either on the indeks yolk, white indeks eggs, haugh unit and air sac.